2022
DOI: 10.1001/jamanetworkopen.2022.1490
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3 Randomized Clinical Trials of Frontline Therapies for Malignant Pleural Mesothelioma

Abstract: IMPORTANCE Some recently proposed frontline therapies for malignant pleural mesothelioma (MPM) are very costly, yet their impact on quality of life and overall survival of these patients remains arguable. Given the high social toll of this aggressive occupational cancer, it is paramount to establish the real clinical benefit of these treatments. OBJECTIVETo directly compare and analyze the statistical robustness of the 3 randomized clinical trials (RCTs) of frontline therapies recommended for MPM since 2003. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 21 publications
0
28
0
Order By: Relevance
“…Messori et al found that nivolumab plus ipilimumab or pembrolizumab monotherapy showed a small but significant survival benefit, but not durvalumab plus pemetrexed plus cisplatin, compared to standard of care treatment (pemetrexed plus cisplatin) [96]. However, Meirson et al [97] and Kerrigan et al [98] reported no survival benefit for nivolumab plus ipilimumab or either a single agent alone compared to bevacizumab plus cisplatin plus pemetrexed or single-agent chemotherapy. MMe patients in these trials were not stratified by their MSI status or tumor mutation burden.…”
Section: Discussionmentioning
confidence: 99%
“…Messori et al found that nivolumab plus ipilimumab or pembrolizumab monotherapy showed a small but significant survival benefit, but not durvalumab plus pemetrexed plus cisplatin, compared to standard of care treatment (pemetrexed plus cisplatin) [96]. However, Meirson et al [97] and Kerrigan et al [98] reported no survival benefit for nivolumab plus ipilimumab or either a single agent alone compared to bevacizumab plus cisplatin plus pemetrexed or single-agent chemotherapy. MMe patients in these trials were not stratified by their MSI status or tumor mutation burden.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the median overall survival after treatment with nivolumab plus ipilimumab was consistent between epithelioid histology tumors (18.7 months) and nonepithelioid tumors (18.1 months) (73). Nevertheless, a recent comparative effectiveness study was conducted to compare the 3 main clinical trials of first line setting for MPM: the SoC cisplatin and pemetrexed (MPS), nivolumab and ipilimumab (CM73) and bevacizumab combined with the SoC (MAPS) (74). Through an accurate reconstruction of Kaplan-Meier curves, no significant improvements in terms of overall survival was detected for one treatment over the other.…”
Section: Immune Checkpoint Inhibitors As a First-line Treatmentmentioning
confidence: 99%
“…Through an accurate reconstruction of Kaplan-Meier curves, no significant improvements in terms of overall survival was detected for one treatment over the other. Moreover, potential biases on censored patients have been detected, leading to hesitations that should be further investigated and clarified to strengthen the reliability of the study (74). As well as that, another study aimed at comparing individual patient data reconstructed retrospectively from 4 clinical trials: the same considered in the other study and durvalumab combined with SoC.…”
Section: Immune Checkpoint Inhibitors As a First-line Treatmentmentioning
confidence: 99%
“…MPM exhibits long clinical latency and significant resistance to therapy, with the latter impacting only to a limited extent the natural history of the disease. As a result, prognosis for MPM patients results in poor PFS and OS [1,7,8] . The mainstay of MPM treatment is still represented, for first-line or inoperable patients, by cisplatin and antifolate [1,9] .…”
Section: Introductionmentioning
confidence: 99%